2018
DOI: 10.1136/bmjopen-2017-019461
|View full text |Cite
|
Sign up to set email alerts
|

Better outcome from arthroscopic partial meniscectomy than skin incisions only? A sham-controlled randomised trial in patients aged 35–55 years with knee pain and an MRI-verified meniscal tear

Abstract: ObjectiveCompare arthroscopic partial meniscectomy to a true sham intervention.MethodsSham-controlled superiority trial performed in three county hospitals in Denmark comparing arthroscopic partial meniscectomy to skin incisions only in patients aged 35–55 years with persistent knee pain and an MRI-confirmed medial meniscus lesion. A computer-generated table of random numbers generated two comparison groups. Participants and outcome assessors were blinded to group allocation. Exclusions were locking knees, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 24 publications
0
68
0
Order By: Relevance
“…Altogether, 7 randomized controlled trials (RCTs) fulfilling the inclusion criteria were found (Table ) . Of the 7 RCTs, 5 have been carried out in the Nordic countries, one in USA, and one in South Korea.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Altogether, 7 randomized controlled trials (RCTs) fulfilling the inclusion criteria were found (Table ) . Of the 7 RCTs, 5 have been carried out in the Nordic countries, one in USA, and one in South Korea.…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported the proportion of patients crossing over to surgical treatment, but none of the studies reported reasons for the crossover. In 5 trials, the proportions of patients crossing over to surgery were highest and varied between 19 and 36 percent. No trial reported prespecified criteria for crossing over to surgical treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations